Effect of Flow Resistance in Adiabatic Part on the Thermal Performance of CO2, R134a, and R410A Two-phase Thermosyphon Loops - Tong Zhen; Wen Xinran; Han Zekun; Fang Chunxue; Song Yulong (Zhileng xuebao)
This study experimentally investigates the impact of flow resistance in risers and downcomers on the heat transfer performance of two-phase thermosyphon loops (TPTLs) with CO2, R134a, and R410A refrigerants. Variations in the heat transfer limit and thermal resistance of the TPTLs were analyzed. The results show that the three TPTLs respond differently to changes in flow resistance. For the CO2 TPTL, the effects of the riser and condenser resistances on thermal performance are similar. When the opening angle of the riser or condenser valve decreases from 90° to 30°, the heat transfer limit of the CO2 TPTL decreases from 1 200 W to 700 W. For the R134a and R410A TPTLs, when the opening angle of the riser valve decreases from 90° to 30°, the heat transfer limit of the R410A TPTL decreases from 1 300 W to 700 W, and the R134a TPTL does not reach normal operating conditions, resulting in substantial superheating and subcooling inside the pipes and a substantial increase in thermal resistance for both types. An increase in the condenser resistance has little effect on the thermal performances of the R134a and R410A TPTLs. For practical design considerations, the same or similar diameters should be used for the riser and downcomer of a CO2 TPTL. However, for R134a and R410A TPTLs, the riser diameter should be significantly larger than the downcomer diameter to achieve material cost savings.